Tourist Perceptions of North Tapanuli Tourism Destinations in the Online Space: A Netnography Research - Rut Irmawati Gultom; Siringoringo, Benny (Journal of Innovative and Creativity, 2025)
This study examines tourists’ perceptions of tourism destinations in the Tapanuli region as articulated in online spaces. Employing a qualitative approach, the research analyzes user-generated content in the form of online reviews, comments, and narrative descriptions collected from publicly accessible digital platforms. The findings indicate that tourists’ perceptions are shaped through a dynamic interaction between positive and negative narratives. Positive perceptions predominantly emphasize natural beauty, scenic landscapes, cultural richness, and emotional experiences of relaxation and tranquility. Conversely, negative perceptions frequently relate to inadequate sanitation, poor facility maintenance, accessibility constraints, and environmental management issues. These contrasting narratives coexist within online spaces, contributing to a multidimensional and continuously negotiated destination image. The study further demonstrates that online spaces function as influential arenas for the formation of collective perceptions, where tourists’ experiences are shared, evaluated, and amplified through digital interaction. The results highlight that the effectiveness of digital tourism promotion depends not only on technological visibility but also on the consistency between online representations and on-site conditions. This research contributes to the literature on digital tourism and destination image by providing empirical insights into how tourists’ perceptions are constructed in online environments and offers practical implications for more responsive and sustainable destination management strategies.